Viability of Toxoplasma gondii in cattle semen cryopreserved with different concentrations of cryoprotectant - Felippelli, Gustavo [UNESP]; Toscano, João Henrique B. [UNESP]; Texeira, Weslen F.P.; Santos, Isabella B. [UNESP]; Cruz, Breno C. [UNESP]; Maciel, Willian G. [UNESP]; Soares, Vando E.; Bresciani, Katia Denise S. [UNESP]; Lopes, Welber D.Z.; Costa, Alvimar José [UNESP] (FapUNIFESP (SciELO), 2023)
Felippelli G., Toscano J.H.B., Texeira W.F.P, Santos I.B., Cruz B.C., Bresciani K.D.S, Lopes W.D.Z. & Costa A.J. 2023. Viability of Toxoplasma gondii in cattle semen cryopreserved with different concentrations of cryoprotectant. Pesquisa Veterinária Brasileira 42:e07106, 2023. Centro de Pesquisas em Sanidade Animal, Departamento de Patologia Veterinária, Faculdade de Ciências Agrárias e Veterinárias, Universidade Estadual Paulista “Júlio de Mesquita Filho”, Campus de Jaboticabal, Via de Acesso Prof. Paulo Donato Castellane s/n, Zona Rural, Jaboticabal, SP 14884-900, Brazil. E-mail: gusvetfelippelli@gmail.com Toxoplasma gondii can be eliminated in bovine semen. Cryopreserved semen is often used due to the fact that artificial insemination in dairy and beef cattle provides benefits in terms of production. However, little is known regarding the viability and infectivity of T. gondii tachyzoites in cryopreserved bovine semen. In the present study, cattle semen negative for T. gondii were contaminated with 1 x 106 tachyzoites (RH strain) and cryopreserved with and without different cryoprotectants, such as DMSO (concentrations of 2.5%, 5.0%, 7.5%, 8.0% and 10.0%) and glycerol (2.25%, 2.5%, 3.0%, 5.0%, 7.5% and 10.0%), followed by freezing in liquid nitrogen (-196°C). After 24 hours, the samples were thawed and inoculated in 10 mice per cryoprotectant concentration. The mice were evaluated for clinical signs of toxoplasmosis (rough coat, diarrhea, hypoactivity and sudden death) as well as serum titers of IgM and IgG and the presence of tachyzoites in the peritoneal lavage. The results revealed that T. gondii remained infective in all samples. Clinical signs of toxoplasmosis were observed in the mice beginning with the 6th day post-inoculation (DPI) and 100% lethality was found between the 7th and 9th DPI. Viable tachyzoites were recovered from peritoneal exudate of dead mice (except for the control group), with higher mean of tachyzoite counts in the intraperitoneal lavage for 5% DMSO (±3.32 x 106), 8% DMSO (±3.53 x 106), 3% glycerol (±4.75 x 106), 7.5% glycerol (±6.26 x 106) and the absence of cryoprotectant (±3.11 x 106). Seroconversion occurred in the treated groups, with titers of IgG from 1:16 to 1:128 and IgM from 1:16 to 1:512. T. gondii viability and infectivity were maintained in cattle semen during 24 hours of cryopreservation at -196°C with and without cryoprotectant. However, further studies are necessary to determine whether cryopreserved semen contributes to the spread of toxoplasmosis through artificial insemination.
Keywords: cattle; cryopreservation; cryoprotectant; DMSO; glycerol; IFI; RH strain; semen samples; Toxoplasma gondii; toxoplasmosis